Correction: Quartz crystal microbalance for telomerase sensing based on gold nanoparticle induced signal amplification. Issue 11 (29th January 2021) - Yang, Haitang; Li, Ying; Wang, Dingzhong; Liu, Yong; Wei, Wei; Zhang, Yuanjian; Liu, Songqin; Li, Peng
Abstract : Correction for 'Quartz crystal microbalance for telomerase sensing based on gold nanoparticle induced signal amplification' by Haitang Yang et al., Chem. Commun., 2019, 55, 5994–5997, DOI: ; 10.1039/C9CC02610J .